Transverse limb defect: a case report - Poojari, Vidyashree Ganesh; Pai, Muralidhar V.; Vasudeva, Akhila; Nambiar, Jayaraman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Transverse limb defects are a relatively rare problem (3.5-6.9/10000 births) with a fairly low prenatal detection rate (55%). The possible etiology for this condition could be as part of a genetic condition or amniotic band syndrome. The detection rate can be improved with the use of careful anatomical survey during anomaly scan. In this case report, transverse limb defect was detected in the second trimester.